1993
DOI: 10.1002/ana.410340212
|View full text |Cite
|
Sign up to set email alerts
|

Visual evoked potentials in adrenolukodystrophy: A trial with glycerol trioleate and Lorenzo oil

Abstract: Adrenoleukodystrophy is an X-linked metabolic disorder with very-long-chain fatty acid (VLCFA) accumulation and multifocal nervous system demyelination, often with early involvement of visual pathways. Dietary therapy with glycerol trioleate and glycerol trierucate (Lorenzo oil) diminishes VLCFA levels. In a study of patients with the adrenomyeloneuropathy phenotype of adrenoleukodystrophy, we used pattern-reversal visual evoked potentials to evaluate visual pathways before and after treatment. Of 108 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…In patients with X-ALD, LO rapidly normalizes plasma VLCFA and effectively reduces tissue levels of VLCFA, except in the brain (36)(37)(38)(39)(40). These early, limited clinical trials suggested that 22:1n-9, the active component of LO, failed to cross the BBB (36,39,40), thereby accounting for the lack of efficacy in limiting the rapid progression of the demyelination in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with X-ALD, LO rapidly normalizes plasma VLCFA and effectively reduces tissue levels of VLCFA, except in the brain (36)(37)(38)(39)(40). These early, limited clinical trials suggested that 22:1n-9, the active component of LO, failed to cross the BBB (36,39,40), thereby accounting for the lack of efficacy in limiting the rapid progression of the demyelination in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies included glycerol trierucate in a treatment regimen referred to as Lorenzo's Oil (LO) (U.S. Patent number 5,331,009). This treatment normalized plasma 26:0 levels within 4 weeks but did not halt neurological deterioration in patients with advanced X-ALD (36)(37)(38). Postmortem analysis of tissue from these X-ALD patients treated with LO show that erucic acid (22:1n-9) was absorbed from the gut and found esterified into liver, adrenal glands, and adipose lipid pools, but brain levels of 22:1n-9 were not different between treatment groups (39,40).…”
mentioning
confidence: 99%
“…Kaplan et al, 1993 found that pattern-reversal VEPs were abnormal in 17% of patients with adrenoleukodystrophy; no evidence indicated that reduction of VLCFA levels improved or retarded visual pathway demyelination.…”
Section: Vep In Adrenoleukodystrophymentioning
confidence: 96%
“…A practical goal seems to be a reduction of VLCFA to normal plasma levels. gingivitis [85][86][87][88][89][90]. In addition to LO treatment a VCLFA-poor diet with fat restriction to 15% of the daily calories is applied.…”
Section: Therapymentioning
confidence: 99%
“…A series of small clinical trials led to the conclusion that the intake of LO does not completely prevent the progression in all patients who are already neurologically symptomatic at initiation of the therapy [80,[87][88][89]108], however, in the absence of any controlled studies, it is not possible to determine whether the reported progression in some symptomatic patients differs from what one would expect in untreated patients. Moreover, most…”
Section: Therapymentioning
confidence: 99%